Impact of Agronomic Zinc Biofortification on Yield Attributes, Yield and Micronutrient Uptake of Rice (Oryza sativa L.) in Southern Odisha - Pal, Swarnajit; Shankar, Tanmoy; Majumder, Sitabhra; Adhikary, Rahul; Pal, Subhajit (International Journal of Experimental Research and Review, 2024)
Cereal crops are low in micronutrients primarily due to Iron and Zinc deficiency in soil. Iron, being the cofactor of various enzymes, performs basic functions in the human body, while its absence causes anaemia. Symptoms of Zn-deficiency appearing in the human body includes retarded growth, hypogonadism, immune dysfunction and cognitive impairment. In rice plants, their deficiency results in stunted growth and poor plant development, leading to yield reduction. Consumption of milled rice containing very low levels of iron and zinc, is one of the principal reasons for widespread malnutrition among rice consumers. Health of millions of people around the world, including India, is directly or indirectly affected due to ‘Hidden Hunger’ or ‘Malnutrition’ of iron and zinc. The current study was conducted in the summer season of 2022 at the Post Graduate Research Farm, M.S. Swaminathan School of Agriculture, comprising 8 treatments of zinc (foliar and basal) applications on rice. Influence of these treatments on grain and straw yield of rice was ascertained by measuring Pearson correlation coefficient and different multivariate tests viz., Multiple Regression, Multilayer Perceptron Neural Analysis (MPN) and Principal Component Analysis (PCA), which indicated that grain zinc and iron content, was highly influenced by the zinc application. Analysis of generated data indicated that basal application of 5 kg Zn ha?1 along with foliar application of 0.25% Zn at maximum tillering and at booting stage produced the highest grain yield (6.80 t ha-1) and superior outcomes on different yield attributes, nutrient uptake and straw yield of hybrid rice as compared to other treatments, (MARVEL 1011) in the soil of Southern Odisha.